2004
DOI: 10.1001/archneur.61.5.770
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Intramedullary Spinal Neurocysticercosis With Eosinophilic Meningitis

Abstract: Intramedullary neurocysticercosis should be considered as a potentially treatable cause of multilevel spinal lesions with subacute meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…, and this would help explain why the most common region of IC is thoracic, followed by cerv ical, lumbar and sacral regions 2,8,12,15,20,22,23,25 . The cysticercus can cause direct mass effect, induce regional or distant inflammatory reaction, and medullar degeneration due to meningitis or vascular compre ssion and insuff i c i e n c y 5 , 8 , 1 0 , 1 2 , 1 4 , 1 6 , 2 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, and this would help explain why the most common region of IC is thoracic, followed by cerv ical, lumbar and sacral regions 2,8,12,15,20,22,23,25 . The cysticercus can cause direct mass effect, induce regional or distant inflammatory reaction, and medullar degeneration due to meningitis or vascular compre ssion and insuff i c i e n c y 5 , 8 , 1 0 , 1 2 , 1 4 , 1 6 , 2 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It seems that albendazole is more e ffective for IC than praziquantel, as it is for cere b r a l c y s t i c e rc o s i s 1 8 . Dexamethasone is also used because it increases albendazole blood levels and attenuates treatment-associated inflammatory reactions 23 . IC is a rare condition, mainly at the sacral re g i o n , and the difficulties in making a definitive diagnosis a re greater in non-endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, spinal involvement of cysticercosis is exceedingly rare. According to the previous literature, the incidence of spinal cysticercosis ranges from 1 to 3% compared to intracranial cysticercosis 3,15) . Colli et al suggested the hypothesis of "sieve effect" at the transition level between intracranial and intraspinal subarachnoid space to account for the relatively lower incidence of spinal cysticercosis 5) .…”
Section: Discussionmentioning
confidence: 99%
“…There have been some controversies in the literature regarding surgical excision versus medical treatment for spinal cysticercosis 2,4,11,12,15) . The patients with severe neurologic symptoms caused by spinal cysticercosis are the best candidates for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation